No difference between the effects of supplementing with soy protein versus animal protein on gains in muscle mass and strength in response to resistance exercise - Messina, M.; Lynch, H.; Dickinson, J. M.; Reed, K. E. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
Much attention has been given to determining the influence of total protein intake and protein source on gains in lean body mass (LBM) and strength in response to resistance exercise training (RET). Acute studies indicate that whey protein, likely related to its higher leucine content, stimulates muscle protein synthesis to a greater extent than proteins such as soy and casein. Less clear is the extent to which the type of protein supplemented impacts strength and LBM in long-term studies (=6 weeks). Therefore, a meta-analysis was conducted to compare the effect of supplementation with soy protein to animal protein supplementation on strength and LBM in response to RET. Nine studies involving 266 participants suitable for inclusion in the meta-analysis were identified. Five studies compared whey with soy protein, and four studies compared soy protein with other proteins (beef, milk, or dairy protein). Meta-analysis showed that supplementing RET with whey or soy protein resulted in significant increases in strength but found no difference between groups (bench press: 2 = 0.02, p = .90; squat: 2 = 0.22, p = .64). There was no significant effect of whey or soy alone (n = 5) on LBM change and no differences between groups ( 2 = 0.00, p = .96). Strength and LBM both increased significantly in the "other protein" and the soy groups (n = 9), but there were no between-group differences (bench: 2 = 0.02, p = .88; squat: 2 = 0.78, p = .38; and LBM: 2 = 0.06, p = .80). The results of this meta-analysis indicate that soy protein supplementation produces similar gains in strength and LBM in response to RET as whey protein.